Incremental healthcare cost burden in patients with atrial flutter only - Kim, Kathryn M.; Kim, Steven Y.; Schulman, Kathy L.; Kim, Michael H. (Frontiers in Cardiovascular Medicine, 2023)
Background Limited information is available on the costs related to atrial flutter only. This study provides a comprehensive estimate of the cost in patients with atrial flutter only versus matched patients without any atrial arrhythmia. Methods Patients over 20 years of age with a minimum of one inpatient or two outpatient diagnosis codes for atrial flutter in 2005 and a minimum of 12 months of continuous enrollment pre- and post-index were identified using the MarketScan Commercial and Medicare databases. Atrial flutter patients were propensity matched to patients without atrial arrhythmias. Total costs for each patient for 12 months post-index were calculated. National cost was estimated using the projected prevalence of atrial flutter for 2010. Results A total of 1,042 patients with atrial flutter only were successfully matched with comparison patients. For atrial flutter patients compared to matched controls without atrial arrhythmias, total mean annual cost per patient was 81% higher (23,008 vs. 12,717) and mean annual inpatient expenditure was 214% higher (8,518 vs. 2,713). When applied to national atrial flutter prevalence data, total incremental cost burden was estimated to be 687.9 million per year more than patients without atrial arrhythmias, primarily due to cardiovascular specific expenditure (377 million, 55% of total) with 58% (218.5 million) of the increased inpatient expenditure due to cardiovascular specific admissions and 159 million (23%) for atrial flutter specific care. Sex-related differences were also present in atrial flutter only patients. Conclusion Although atrial flutter-only patients are less prevalent than atrial fibrillation patients, the national incremental cost burden in atrial flutter is substantial on a per-patient level.